(untitled) (Historia, 2021)
This is a well-written book on the seminal ideas of the New Era Fellowship (NEF), a public education and cultural project of the Non-European Unity Movement (NEUM) and the Workers’ Party of South Africa (WPSA). A book of this nature is long overdue and is urgently needed given the fact that the political history of South Africa is almost always equated with the African National Congress (ANC) and its sister organisation, in the Congress Alliance, the South African Communist Party (SACP). This book is not a biography of the people who led the NEF. Rather, it is “a sociology of knowledge of the left movement of the 1930s to the 1960s” (p 21). What the author grapples with is the NEF’s sociological reading of South Africa of the period just mentioned.